ASSESSMENT OF MAGNESIUM (MG) AND ZINC (ZN) IN CARCINOMA BREAST PATIENTS - SONGARA, NEERAJ SINGH; BHARGAVA, AJAY KUMAR; CHAUDHARY, AKSHITA; SHARMA, ANUSHREE (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to determine and compare serum magnesium (Mg) and zinc (Zn) concentrations between breast carcinoma patients and healthy controls. Methods: Determination and comparison of serum Mg and Zn was done between 50 breast carcinoma patients and 50 healthy controls. Determination and comparison of LFT in between 50 breast cancer patient during different course of chemotherapy. Trace element analysis was done using atomic absorption spectrophotometry. Statistical comparison was done, results were expressed as Mean±SD, p<0.05 was considered to be statistically significant. Results: All groups were statistically matched in age, sex, and p>0.05. Serum Mg concentrations in cases and controls (0.9920±0.38 mg/dL) and (1.49±0.58 mg/dL) respectively, p≤0.0001* serum Zn concentrations in cases and controls were (66.74±12.58 μg/dL) and (90.88±14.51 μg/dL), respectively, p≤0.0001*. Conclusion: Both serum (Zn) and (Mg) showed significant decreases in breast carcinoma patients as compare to healthy controls.